The Role Of The Kalisabuk Village Community In Developing The Quality Of Islamic Education - Azizul Muchtar; Tutuk Ningsih (Universitas Pahlawan Tuanku Tambusai, 2022)
The general public has a strategic role in efforts to improve the quality of education in madrasah, this implementation will involve community participation and cooperation both morally and materially. The role of the community with education institusions is a series of the entire process of implementing education that is planned and attempled intentionally and seriously. Education has a central role in the nation’s civillization in seeking to increase human resources in a more educated direction. Education is expected to be able to then shape or print someone so that they can develop their attitudes, skills and intellectual awareness to become skilled, intelligent, and noble human beings. In this case, the role of education in Indonesia is not only on the part of students and school institutions, but the community also has an important role in developing education both as a source, implementer and user of educcational outcomes. This is what the two parties have not fully relized, both consider that both are an inseparable part. In order to realize this collaboration between the two parties, it is centrainly necessary to function in the field of public relations as a communication mediator betweeneducational institutions and the community. This study use a qualitative method. The research subject is the Kalisabuk village community. The results of the study indicate that the role given by the community will provide a reference in the development of educational institutions both in Kalisabuk Village, Kesugihan District, Cilacap Regency.